2023
DOI: 10.1021/acsami.2c20722
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Dual-Cross-Linked Hydrogels with Stem Cell Differentiation Regulatory Properties Promote Growth Plate Injury Repair via Controllable Three-Dimensional Mechanics and a Cartilage-like Extracellular Matrix

Abstract: Recent breakthroughs in cell transplantation therapy have revealed the promising potential of bone marrow mesenchymal stem cells (BMSCs) for promoting the regeneration of growth plate cartilage injury. However, the high apoptosis rate and the uncertainty of the differentiation direction of cells often lead to poor therapeutic effects. Cells are often grown under three-dimensional (3D) conditions in vivo, and the stiffness and components of the extracellular matrix (ECM) are important regulators of stem cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Guan-synthesized three-dimensional hydrogels encapsulating bone marrow mesenchymal stem cells (BMSCs) use oxidized chondroitin sulfate via dynamic Schiff base bonding. The transformation of BMSCs into chondrocytes and the repair of damaged growth plates were facilitated [ 47 ]. Hao et al demonstrated that chondroitin sulfate is involved in biomineralization in its free state which promotes bone tissue repair [ 48 ].…”
Section: Hydrogel Materialsmentioning
confidence: 99%
“…Guan-synthesized three-dimensional hydrogels encapsulating bone marrow mesenchymal stem cells (BMSCs) use oxidized chondroitin sulfate via dynamic Schiff base bonding. The transformation of BMSCs into chondrocytes and the repair of damaged growth plates were facilitated [ 47 ]. Hao et al demonstrated that chondroitin sulfate is involved in biomineralization in its free state which promotes bone tissue repair [ 48 ].…”
Section: Hydrogel Materialsmentioning
confidence: 99%
“…Thus, GMOCS hydrogels can achieve sustained release of active ingredients and affect the differentiation trend of MSCs, thus provide a good niche for promoting the repair of growth plates injury and cartilage regeneration. Their safety and feasibility for clinical conversion can be further evaluated in the future 167 (Table 2).…”
Section: Introductionmentioning
confidence: 99%